TRAINER KELISTRIKAN SISTEM STARTER MOBIL TOYOTA KIJANG 5K - , NUR FAJAR SIDIK, Harjono, ST., MT. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
A combustion engine can not move by itself, therefore requires additional power for the first time cranking (start) to turn on the motor. There are several ways to start, generally uses electric starter as prime mover in the motor (engine). Final project that writters make, certain three main topics namely starter motor components, wiring diagrams, and process training kit. The starter motor include several components such magnetic switch, starter Clucths, starter houshing, armatur, field frame (field Coil), brush holder dan end frame. Other scope in this final project is the wiring diagram. procces Training Kit is divided into three main processes, namely welding frame, panel board formation, and installation / assemble the cables From the test results, the circuit assembled works fine and as expected